Fleksibilitas Profit Dalam Ekonomi Islam - Ihwan Wahid Minu (Institut Agama Islam Negeri (IAIN) Bone, 2018)
One purpose of economic activity is to make a profit. Profit can be a pretty important reference in assessing the condition of the success of a business. Profit should be interpreted broadly and holistically not only from the material aspect but also from the mental and spiritual aspects. The purpose of this research is to explain how profit means in Islamic Economics and how the flexibility of the application of profit meanings in Islamic Economics. This research uses research methods with qualitative approaches and literature and qualitative data analysis as an analytical tool. The results of the study show that profits in Islamic Economics are divided into two, namely material profits and spiritual benefits. The application of the meaning of profit in Islamic Economics is flexible which depends on conditions and runs according to principles